The Impact of Serum Anti-neutrophil Cytoplasmic Antibody on Clinical Characteristics and Outcomes in Pediatric-Onset Systemic Lupus Erythematosus Patients - Gau, Chun-Chun; Tseng, Min-Hua; Wu, Chao-Yi; Yang, Huang-Yu; Huang, Jing-Long (Frontiers in Medicine, 2021)
Background: Systemic lupus erythematosus (SLE), an autoimmune disease, is characterized by the overproduction of autoantibodies. Anti-neutrophil cytoplasmic antibodies (ANCAs) have been recognized in SLE for decades. To date, their association with SLE disease activity, especially in pediatric-onset SLE (pSLE) patients, is limited. Methods: We conducted a retrospective case-control study of pSLE patients with ANCAs from 2010 to 2020. Clinical characteristics, laboratory data, renal histological features, treatment and outcomes were analyzed. Results: A total of 70 pediatric-onset SLE patients (9 ANCA-positive versus 61 ANCA-negative) with a median age of 12.23 years (age ranging from 4 years to 18 years) at diagnosis were enrolled. Among patients with ANCAs, MPO-ANCA was found in seven and PR3-ANCA in two of those cases. Patients with ANCAs had a tendency to have hematuria compared with those without ANCAs (66% vs 24.6%, respectively; p = 0.026). Of the 70 SLE patients, 8 with ANCAs and 44 without ANCAs underwent renal biopsies. Patients with ANCAs (25%, 2/8) were more likely to lack the typical full-house pattern in their renal immunofluorescence (IF) staining. Besides, four patients with prominent p-ANCA were presented and discussed. Conclusion: pSLE patients with ANCAs tend to have hematuria and an absence of typical IF histology. However, patients with and without ANCAs showed no difference in their clinical presentations and treatment outcomes.